Komposisi Mikroalga Epilitik di Sungai Mentuka Kabupaten Sekadau - Ari Hepi Yanti, Diah Pratiwi, Tri Rima Setyawati (Universitas Tanjungpura, 2017)
Ephilitic microalgae is a microalgae that lives on a stone surface and it has an important role in aquatic ecosystem. The aim of this study are to know the composition of ephilitic microalgae and the condition of physical-chemical water in Mentuka River. This study was conducted 3 months from November 2016 to January 2017. This study used purposive random sampling method. The result shows that ephilitic microalgae which found in Mentuka River can be classify into two classes, namely Bacillariophyceae (15 genera) and Zygnematophyceae (4 genera). Synedra has the highest of average abundance in Mentuka River and the lowest is Fragilaria. Diversity and Evenness Index of ephilitic microalgae in every station categorized medium (H’= 1,53-1,65 dan E=0,52-0,56), meanwhile categorized of Dominance Index is low (C=0,29-0,34). The environmental condition in Mentuka River supports the life of ephilitic microalgae with temperature 26-28˚C, stream discharge is about 6,1-7 m/s, pH is about 6,8-7,3, dissolved oxygen is about 6,1-7 mg/L and CO2 is 3,9-5,0 mg/L.